Positive Politeness Strategies Used In The Perfect Date Movie - Ni Luh Dina Velia Rayani; I Made Netra; Ni Ketut Sri Rahayuni (Lembaga Pengembangan Kinerja Dosen, 2023)
Positive politeness tends to minimize social distance, meanwhile negative politeness expands the social distance, however still showing respect behavior towards the interlocutor. The aim of this study is to find out positive politeness strategies used by the main character in The Perfect Date movie. The data of this study were taken from a movie and the script entitled The Perfect Date Movie. This study used the observation and note taking as a technique of collecting data. The method used to analyze the data in this study was qualitative method. This study was conducted based on politeness theory proposed by Brown and Levinson (1987). The result of this study showed that all the fifteen strategies are used by the characters in the movie. Almost all politeness strategies used in the main characters' utterances. That is because the interlocutors of the main characters in the film are mostly family, schoolmates, and people of the same age as the speakers.